2012
DOI: 10.1210/en.2011-1752
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal Cell Aldosterone Production Is Stimulated by Very-Low-Density Lipoprotein (VLDL)

Abstract: Very low-density lipoproteins (VLDL) are a class of large lipoprotein synthesized in the liver. The key function of VLDL, in vivo, is to carry triglyceride from the liver to adipose tissue. As a steroidogenic organ, the adrenal gland mainly uses lipoproteins as sources of cholesterol. Although VLDL receptors have been detected in the human adrenal, the function of VLDL in the adrenal gland remains unknown. Herein, we used primary cultures of human and bovine adrenal cells and the adrenocortical cell line H295R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
46
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 54 publications
4
46
0
1
Order By: Relevance
“…Phospholipase D has also been found to mediate aldosterone production and CYP11B2 expression in response to VLDL (Tsai et al 2014), similarly to its role in AngII-induced steroidogenesis. Finally, we also showed that rats on a chow and liquid-sucrose diet that induces obesity and insulin resistance exhibit increased aldosterone synthase levels correlating with elevated triglyceride levels (a measure of VLDL levels in fasted animals) in vivo (Xing et al 2012).…”
Section: :1mentioning
confidence: 65%
See 4 more Smart Citations
“…Phospholipase D has also been found to mediate aldosterone production and CYP11B2 expression in response to VLDL (Tsai et al 2014), similarly to its role in AngII-induced steroidogenesis. Finally, we also showed that rats on a chow and liquid-sucrose diet that induces obesity and insulin resistance exhibit increased aldosterone synthase levels correlating with elevated triglyceride levels (a measure of VLDL levels in fasted animals) in vivo (Xing et al 2012).…”
Section: :1mentioning
confidence: 65%
“…In the H295R cell line, the effects of VLDL on CYP11B2 transcript levels are not additive with high AngII or elevated extracellular potassium levels, but are additive with the cAMP-elevating agents ACTH and forskolin (Xing et al 2012) and are not altered by exposure to an AT1R antagonist (Tsai et al 2014). The effect of VLDL on aldosterone and CYP11B2 involves the calcium signaling pathway, as the changes can be inhibited by antagonists 230:1 of voltage-dependent L-type calcium channels and calcium/calmodulin-dependent protein kinases (Xing et al 2012). Phospholipase D has also been found to mediate aldosterone production and CYP11B2 expression in response to VLDL (Tsai et al 2014), similarly to its role in AngII-induced steroidogenesis.…”
Section: :1mentioning
confidence: 97%
See 3 more Smart Citations